The Cambridge companion to Nozick's Anarchy, state, and utopia - Bader, Ralf M.; Meadowcroft, John (Cambridge companions, 2011)
"Robert Nozick's Anarchy, State, and Utopia (1974) is recognised as a classic of modern political philosophy. Along with John Rawls's A Theory of Justice (1971), it is widely credited with breathing new life into the discipline in the second half of the twentieth century. This Companion presents a balanced and comprehensive assessment of Nozick's contribution to political philosophy. In engaging and accessible chapters, the contributors analyse Nozick's ideas from a variety of perspectives and explore neglected areas of the work such as his discussion of anarchism and his theory of utopia. Their detailed and illuminating picture of Anarchy, State, and Utopia, its impact and its enduring influence will be invaluable to students and scholars in both political philosophy and political theory"--